Microcapsules: Reactive Gelation Synthesis of Monodisperse Polymeric Capsules Using Droplet‐Based Microfluidics (Adv. Mater. Technol. 6/2019). Issue 6 (11th June 2019) - Yang, Tianjin; Cingolani, Alberto; Casalini, Tommaso; Aribia, Abdessalem; Klaue, Antoine; Wu, Hua; Stavrakis, Stavros; de Mello, Andrew; Morbidelli, Massimo
Abstract : In article number1900092, Andrew de Mello, Massimo Morbidelli and co‐workers review a novel method for the fabrication of microporous particles using droplet‐based microfluidic reactors. The combination of microfluidic emulsification with reaction gelation constitutes a robust and efficient method for the fabrication of monodisperse hollow spherical polymeric capsules with tunable porosity and precise control over capsule size.